Can graphene outperform indium tin oxide as transparent electrode in organic solar cells?. (2nd November 2015) - Paletti, Paolo; Pawar, Ravinder; Ulisse, Giacomo; Brunetti, Francesca; Iannaccone, Giuseppe; Fiori, Gianluca
Abstract: Graphene holds promises as a transparent electrode in flexible solar cells due to its high mobility and transparency. However, the experimental power conversion efficiency of cells with graphene electrode is still small (<7%). In this paper, we evaluate possible engineering options to improve the power conversion efficiency, by means of multi-scale simulation approach including ab-initio simulations of graphene contacts to improve electrode workfunction and conductance, electromagnetic simulations to improve light management, and electrical simulations of complete cells. We find that the combined effect of using a transparent electrode of graphene with a few monolayers of MoO3 on top to optimize work function and resistivity, and of applying optimized grating to the graphene electrode, can increase power efficiency by up to 29%–47%, with respect to the ITO benchmark, depending on the material used for the hole transport layer (P3HT, PTB7, and Perovskite).